2013
DOI: 10.3389/fpsyg.2013.00975
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing latent state-trait and multiple-indicator latent growth curve models as multilevel structural equation models

Abstract: Latent state-trait (LST) and latent growth curve (LGC) models are frequently used in the analysis of longitudinal data. Although it is well-known that standard single-indicator LGC models can be analyzed within either the structural equation modeling (SEM) or multilevel (ML; hierarchical linear modeling) frameworks, few researchers realize that LST and multivariate LGC models, which use multiple indicators at each time point, can also be specified as ML models. In the present paper, we demonstrate that using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 40 publications
1
70
0
Order By: Relevance
“…Thus, the domains seem to be differently prone to occasion-specific influences. Also, we observed that T1 and T3 values across domains are affected by situation or person and situation interactions (as they are indistinguishable in the LTS models [ 58 ]), whereas T2 scores are more strongly linked to stable disposition (52–81%), as well as method (12–43%). Taken together, this may suggest problematic homogeneity of domain indicators.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the domains seem to be differently prone to occasion-specific influences. Also, we observed that T1 and T3 values across domains are affected by situation or person and situation interactions (as they are indistinguishable in the LTS models [ 58 ]), whereas T2 scores are more strongly linked to stable disposition (52–81%), as well as method (12–43%). Taken together, this may suggest problematic homogeneity of domain indicators.…”
Section: Resultsmentioning
confidence: 99%
“…As the strong MI allows for mean comparison, for this purpose, the mean of the first latent state factor was fixed to be zero, whereas the means of the two remaining latent state factors were freed [ 58 ]. Consequently, the intercepts of those factors can be then interpreted as a difference relative to the first factor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Unfortunately, there is currently no method for estimating a multilevel random slope model with categorical indicators that includes global measures of fit such as Chi-square, RMSEA, CFI, or TLI (Geiser, Bishop, Lockhart, Shiffman, & Grenard, 2013). Although global fit indices are not available when using MLR with random slopes, an iterative approach is possible to examine if nested models significantly improve fit using the Wald test of nested models.…”
Section: Methodsmentioning
confidence: 99%